Treatment of Patients with Rotator Cuff Injuries (Review of Literature) - D. V. Menshova; I. A. Kuklin; N. S. Ponomarenko (Acta Biomedica Scientifica, 2021)
The proportion of injuries to the rotator cuff of the shoulder occupies one of the leading places in the structure of injuries to the musculoskeletal system. The history of the study of this pathology began about five centuries ago and continues to the present day. However, attempts to introduce a generally accepted classification of injuries have not been crowned with success. With the development of scientific and technological progress, many methods of conservative and surgical treatment have appeared. Among the conservative methods of treatment aimed at reducing pain and improving the quality of life, injections of corticosteroids, hyaluronic acid, and autoplasma therapy are used. But, unfortunately, these treatment methods are not aimed at restoring the function of the shoulder joint. Surgical treatments for rotator cuff injuries are varied. This includes both the classic reinsertion of the damaged tendon and arthroscopic treatments. In case of massive ruptures, reconstructive plastic surgery is performed with the transfer of the tendons of the infraspinatus, small round or latissimus dorsi muscle, and autografts or allografts are also used. However, despite the large number of treatment methods, there are no clear algorithms for managing patients with this pathology, and the percentage of unsatisfactory treatment outcomes remains high.